PENGOLAHAN LEACHATE TERCEMAR Pb SEBAGAI UPAYA PENCEGAHAN PENCEMARAN LINGKUNGAN TPA - Ganefati, Sri Puji (Jurnal Teknologi Lingkungan, 2008)
Waste as one of human activity products should be managed in order to minimize its negative impacts to the environment and human health. Environmental pollution will also take place due to waste which contains hazardous substances, such as used battery, accu and broken TL bulbs. Production of those goods uses plublum (Pb) in its process, so that the Pb will be carried later by the leachate flow to the environment. This work was an experiment with pre and post tests design which also used reference group as a control towards Pb parameter. Statistical analyzes was carried out using Anova and T tests with the degree of confidence of 95%. Result of the anova test of reference group with a variation of detention time was probability of about 0.293, whereas the experimental group resulted a probability of 0.005. The T-test for both reference and experimental groups with a variation of detention timegave different values of Pb parameter where the different with the probability of 0.000. The result showed that concentration of Pb in leachate decreased after it was treated using alum and lime. the significant reduction is at leaving time of 3 hours, i.e. 798.3 mg/L (75.7%). Therefore, it ca be concluded that treatment using alum and lime can be applied to reduce concentration of Pb in a lechate.